Substrate and inhibitor binding to the serotonin transporter: Insights from computational, crystallographic, and functional studies. (15th December 2019) - Zeppelin, Talia; Ladefoged, Lucy Kate; Sinning, Steffen; Schiøtt, Birgit
Abstract: The serotonin transporter (SERT) belongs to the monoamine transporter family, which also includes the dopamine and norepinephrine transporters. SERT is essential for regulating serotonergic signaling by the reuptake of serotonin from the synaptic cleft back into the presynaptic neuron. Dysregulation of SERT has been implicated in several major psychiatric disorders such as major depressive disorder (MDD). MDD was among the top five leading causes of years lived with disease in 2016 and is characterized as a major global burden. Several drugs have been developed to target SERT for use in the treatment of MDD, and their respective binding modes and locations within SERT have been studied. The elucidation of the first structure of a bacterial SERT homologue in 2005 has accelerated crystallographic, computational, and functional studies to further elucidate drug binding and method of action in SERT. Herein, we aim to highlight and compare these studies with an emphasis on what the different experimental methods conclude on substrate and inhibitor binding modes, and the potential caveats of using the different types of studies are discussed. We focus this review on the binding of cognate substrate and drugs belonging to the different families of antidepressants, including tricyclic antidepressants, selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, and multimodal drugs, as well as illicit drugs such as cocaine, amphetamines, and ibogaine. This article is part of the issue entitled 'Special Issue on Neurotransmitter Transporters'. Graphical abstract: Image 1047685 Highlights: All studied inhibitors and substrates appear to bind to the primary binding site in hSERT. Escitalopram can bind to an allosteric, vestibular site in hSERT. Substrates utilize subsite A and B in the primary binding site. Inhibitors often interact with subsites A-C, but interaction with subsite C is not required. Substrates and inhibitors are distinguished by three key differences in interaction patterns.